دراسة تحليلية مقارنة لأنشطة إدارة الموارد البشرية الخضراء، بين جامعتي (شقراء وابوظبي) (بالتطبيق على أعضاء هيئة التدريس بجامعة شقراء (المملكة العربية السعودية)، وجامعة ابوظبي (دولة الإمارات العربية المتحدة): A comparative analytical study of the activities of green human resources management, between the universities (Shaqra and Abu Dhabi) (Applied to faculty members at The University of Shaqra (KSA) and Abu Dhabi University (UAE)) - عاصم التجاني إبراهيم شمعون (Journal of North African Economies, 2025)
The study aims to identify the activities of green human resources management between The Universities of Shaqra and Abu Dhabi, and to test the impact between these activities personal and organizational variables. The problem was to cover the shortage of awareness of the impact of personal and organizational variables on the activities of green human resources management in universities . The study found that there are no statistically significant differences in the average opinions of individuals in the sample for the activities attributed to the educational level change, at The Shaqra University. While there are differences in activities (green employment, green incentives, green selection, green performance assessment), referred to the educational level changer, and to the benefit of the master's degree holders, at Abu Dhabi University. Also, there are no differences in the average opinions of the sample members of activities attributable to the change in the number of years of experience, at The University of Shaqra, while there are differences in the respondents' answers about the impact of the personal and organizational variables of the variable (green function design) due to the variable number of years of experience, and for the benefit of the group (10 to under 15 years), at The University of Abu Dhabi.